PRICE GOUGING DURING THE CORONAVIRUS PANDEMIC - J. Cesario, Anthony; Block, Walter E. (Journal of Critical Realism in Socio-Economics (JOCRISE), 2024)
Following the coronavirus outbreak, the demand for certain products such as hand sanitizer, disinfectant wipes, and toilet paper dramatically increased. Due to anti-price-gouging legislation and the fear of the backlash associated with being accused of this practice, however, most retailers have not increased the prices on these commodities. As a result, there has been a massive shortage of these essential items as the first people to arrive buy them all up and leave none for those who arrive later. This means that many of those who may need them more (and would be willing to pay way more than others) are unable to find them. Some stores have tried to limit the number of goods that can be purchased, but since the price hasn't increased, there is still a large shortage. In an attempt to improve the situation some dissatisfied customers travel to different stores and buy up as much of the product as possible and then sell it online for higher prices so that those who value them more than others can get them. Unfortunately, though, online retailers such as eBay and Amazon have cracked down on such price gouging and are consequently making the situation worse. This paper first examines anti-price gouging laws and the effects they have on the price system, such as creating shortages of hand sanitizer, disinfectant wipes, and toilet paper during the coronavirus pandemic critiques. It then analyzes several arguments that have been made in favor of anti-price gouging laws